Factors affecting the adoption of e-learning in Indonesia: Lesson from Covid-19 - Yubaedi Siron; Agus Wibowo; Bagus Shandy Narmaditya (OmniaScience, 2020)
This study aims to examine factors affecting the use of e-learning during the Covid-19 pandemic in Indonesia. This survey study utilized a quantitative approach to understand the relationship variables by using SEM-PLS. An online questionnaire was distributed to collect information from respondents. A total of 250 questionnaires were gathered and 210 responses can be used for further analysis. The findings indicate that the students' intention in using e-learning was determined by several variables, including perceived enjoyment, students experience, computer anxiety, and perceived self-efficacy. These findings also confirm that both perceived ease of use and perceived usefulness can explain the students' intention in utilizing e-learning. The results provide an implication toward the importance of understanding factors of adoption of e-learning and how students can perceive e-learning as the response of the Covid-19 pandemic.